Effects of Trichomonas gallinae infection and diet on blood microbiome composition in european greenfinches (Chloris chloris) - Krama, Tatjana; Krams, Ronalds; Popovs, Sergejs; Gudrā, Dita; Ustinova, Maija; Fridmanis, Davids; Trakimas, Giedrius; Contreras-Garduño, Jorge; Cirule, Dina; Rantala, Markus J.; Adams, Colton B.; Jõers, Priit; et al. (FRONTIERS MEDIA SA, 2025)
Recent research has reported microbial invasion of the bloodstream in various disease-associated conditions. In this study, we investigated the role of trichomonosis outbreak (caused by the Trichomonas gallinae parasite) and food availability in shaping the blood microbiome composition of wintering greenfinches (Chloris chloris). Data were collected during two periods: before the outbreak (December) and during the outbreak (February). No bacterial contamination was observed in pre-epidemic blood samples. All individuals were infected during the outbreak, but greenfinches with irregular food access exhibited lower bacterial contamination in their blood. Individuals with permanent food access had a greater proportional representation of specific microbial taxa and higher alpha diversity in their blood microbiomes. However, beta diversity did not differ between the two groups. We demonstrated that trichomonosis infection and feeding regime play critical roles in mediating septic conditions of peripheral circulation during an outbreak, with food accessibility influencing blood microbial contamination. These findings integrate the impacts of feeding regimes and hematological responses to improve our understanding of the complex interactions between diet, disease, and physiological resilience in wild birds.